Waste plastic recycling process

The chemical waste plastic regeneration process enhances the purity and color quality of recycled plastics by using solvent dissolution, adsorption purification, and recrystallization with specific compounds, addressing the limitations of conventional methods.

JP7669481B2Active Publication Date: 2025-04-28LG CHEM LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023519549
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-06-22
Filing Date
2022-06-21
Publication Date
2025-04-28
Estimated Expiration
2042-06-21

AI Technical Summary

Technical Problem

Conventional waste plastic regeneration processes struggle to achieve high purity and desired color in recycled plastics, leading to environmental issues and limited usage due to high unit prices and mixed color contamination.

Method used

A chemical waste plastic regeneration process involving the dissolution of waste plastic in an organic solvent, followed by adsorption purification using an adsorbent and recrystallization with a compound having a Hansen Solubility Parameter (HSP) of 5 to 14 for polycarbonate, to produce high-purity, colorless recycled plastic.

Benefits of technology

The process significantly increases the purity of recycled plastics, achieves colorless recycled plastic without pigments or dyes, and shortens the regeneration time compared to existing methods, while effectively removing impurities and maintaining the inherent properties of polycarbonate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007669481000001
    Figure 0007669481000001
  • Figure 0007669481000002
    Figure 0007669481000002
  • Figure 0007669481000003
    Figure 0007669481000003
Patent Text Reader

Abstract

The present invention provides a process for recycling waste plastics and a method for producing recycled plastics including the process.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a process for recycling waste plastics, and more particularly to a process for chemically recycling waste plastics using recrystallization and adsorption purification.

[0002] This application claims the benefit of the filing date of Korean Patent Application No. 10-2021-0080482 filed with the Korean Intellectual Property Office on June 22, 2021, the entire contents of which are incorporated herein by reference. [Background technology]

[0003] Plastics are widely used in modern society because they are easy to process and their physical and chemical properties change easily. In order to process waste plastics that are discarded after use, landfilling or incineration is often used, but since plastics are difficult to decompose naturally, landfilling can cause environmental problems such as water and soil pollution, and incineration can cause environmental problems such as air pollution.

[0004] In order to solve these environmental problems, much research has been conducted on recycling waste plastics by processing, refining, or transforming them, and some recycling methods are actually being used. However, the recycled plastics have been expensive and the purity of the plastics cannot be significantly improved, so they have not been widely used. In addition, recycled plastics have the disadvantage that it is difficult to specify the desired physical and chemical properties and achieve the desired color because waste plastics with various colors are mixed, processed, and refined.

[0005] Therefore, there is a continuing need for research into waste plastic recycling processes that can significantly increase the purity of the recycled plastic while achieving the desired color. Summary of the Invention [Problem to be solved by the invention]

[0006] The present invention is aimed at solving the problems of the conventional waste plastic recycling process, and provides a waste plastic recycling process that can greatly increase the purity of the recycled plastic by using a chemical refining method. [Means for solving the problem]

[0007] One embodiment of the present invention includes the steps of dissolving waste plastic in an organic solvent to prepare a first solution; adding an adsorbent to the first solution; recrystallizing the plastic by adding 60 parts by weight or more of a compound having a Hansen Solubility Parameter (HSP) of 5 to 14 in polycarbonate based on 100 parts by weight of the first solution; and A process for recycling waste plastics is provided, which includes recovering the recrystallized plastic.

[0008] Another embodiment of the present invention provides a method for producing recycled plastic, comprising the step of recycling the waste plastic. Effect of the Invention

[0009] The waste plastic recycling process of the present invention can greatly increase the purity of the recycled plastic by using recrystallization and chemical refining methods using adsorbents, and can obtain colorless recycled plastic.

[0010] Furthermore, according to the waste plastic recycling process of the present invention, the organic solvent is added only once, which has the effect of shortening the process compared to the conventional method in which the organic solvent is added twice.

[0011] In addition, according to the waste plastic recycling process of the present invention, it is possible to set optimal adsorption conditions by diversifying the type and content of the adsorbent added, thereby effectively removing impurities contained in waste plastic while maintaining the inherent properties of existing polycarbonate. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] Specific embodiments will now be described in more detail.

[0013] One embodiment of the present invention includes the steps of dissolving waste plastic in an organic solvent to prepare a first solution; adding an adsorbent to the first solution; recrystallizing the plastic by adding 60 parts by weight or more of a compound having a Hansen Solubility Parameter (HSP) of 5 to 14 in polycarbonate based on 100 parts by weight of the first solution; and A process for recycling waste plastics is provided, which includes recovering the recrystallized plastic.

[0014] The present invention is a chemical method for recycling waste plastics using chemical reactions, rather than a mechanical method for recycling waste plastics by physically changing them.

[0015] Specifically, the present invention has an advantage in that it is possible to obtain colorless recycled plastics with higher plastic purity than conventional chemical plastic recycling methods by applying an adsorption purification method using an adsorbent and recrystallization of plastics. The colorless recycled plastic means recycled plastics that do not contain pigments or dyes. More specifically, the "colorless" recycled plastics will be explained in detail based on the measurements of a spectrophotometer described below.

[0016] More specifically, the waste plastic recycling process according to the present invention includes a step of first performing an adsorption purification process by adding an adsorbent to the first solution, and then adding 60 parts by weight or more of a compound having a Hansen Solubility Parameter (HSP) of 5 to 14 in polycarbonate based on 100 parts by weight of the total weight of the first solution to recrystallize the plastic, thereby obtaining plastic with a significantly improved purity.

[0017] In this case, when the first solution contains a compound having a Hansen Solubility Parameter (HSP) of 5 to 14 in polycarbonate in the above-mentioned range based on a total weight of 100 parts by weight of the first solution, additives such as antioxidants or heat stabilizers can be effectively removed from the waste plastic, and recrystallized plastic can be obtained with a high yield. When the first solution contains less than 60 parts by weight, recrystallization is impossible or the yield is low and the recrystallized plastic may contain a large amount of impurities.

[0018] Furthermore, the waste plastic recycling process according to the present invention can diversify the types of adsorbents in the adsorption step and adjust the ratio of each type to set optimal adsorption conditions, thereby removing impurities or other stabilizers and pigments contained in the waste plastic while maintaining the inherent properties of existing polycarbonate, thereby regenerating pure polycarbonate.

[0019] In one embodiment of the present invention, the plastic is a general term for organic polymeric substances that have plasticity, can be softened by heating, and can be molded into any shape.

[0020] The plastic may be, for example, but is not limited to, polycarbonate (PC), polyethylene (PE), polypropylene (PP), polyvinyl chloride (PVC), polystyrene (PS), or polyethylene terephthalate (PET).

[0021] In one embodiment of the present invention, the waste plastic refers to waste generated after the use of plastic, and the waste may be industrial, commercial, or domestic waste, but is not limited to these examples.

[0022] In one embodiment of the present invention, the waste plastic may be waste polycarbonate.

[0023] In this specification, plastics regenerated by the waste plastic recycling process are referred to as "recycled plastics" or "regenerated plastics."

[0024] In one embodiment of the present invention, the weight average molecular weight of the waste polycarbonate may be 40,000 g / mol to 60,000 g / mol. The weight average molecular weight (Mw) can be measured using gel permeation chromatography. Specifically, the weight average molecular weight can be measured using a THF-GPC instrument with a PLgel Mixed B×2 column, tetrahydrofuran (THF) solvent, a flow rate of 1.0 mL / min, and a temperature of 40°C.

[0025] In one embodiment of the present invention, the polydispersity index (PDI) of the waste polycarbonate may be 1.7 to 3. Specifically, the polydispersity index of the waste polycarbonate may be 1.8 to 3.

[0026] In one embodiment of the present invention, the melt flow rate (MFR) of the waste polycarbonate may be 6 to 30. Specifically, the melt flow rate (MFR) of the waste polycarbonate may be 10 to 28.

[0027] The melt flow rate was measured according to ASTM D1238-94A / ISO 1133 method using a Toyoseki MFR instrument at 300° C. with a 1.2 kg weight.

[0028] When the waste polycarbonate of the present invention satisfies at least one of the above-mentioned weight average molecular weight, polydispersity index, and melt flow rate, it is a waste plastic that can be suitably adopted in the waste plastic recycling process of the present invention.

[0029] In one embodiment of the invention, the recrystallized plastic is polycarbonate.

[0030] The polycarbonate refers to a polymer containing a carbonate bond, that is, a carbonate ester bond, in the main chain.

[0031] In one embodiment of the present invention, the organic solvent is a cyclic ether solvent, a linear or cyclic carbonate solvent, or a hydrocarbon solvent having 1 to 8 carbon atoms and containing one or more halogens.

[0032] In one embodiment of the present specification, the cyclic ether solvent may be tetrahydrofuran.

[0033] In one embodiment of the present invention, the linear carbonate solvent may be, but is not limited to, dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), ethyl propyl carbonate (EPC), ethyl methyl carbonate (EMC), or methyl propyl carbonate (MPC).

[0034] In one embodiment of the present invention, the cyclic carbonate solvent may be, but is not limited to, ethylene carbonate (EC), propylene carbonate (PC), 1,2-butylene carbonate (BC), 2,3-butylene carbonate, 1,2-pentylene carbonate, 2,3-pentylene carbonate, vinylene carbonate (VC), vinylethylene carbonate, or fluoroethylene carbonate.Preferably, the cyclic carbonate solvent may be propylene carbonate.

[0035] In one embodiment of the present invention, the hydrocarbon solvent having 1 to 8 carbon atoms and containing one or more halogens may be, but is not limited to, methylene chloride or ethylene chloride.

[0036] In one embodiment of the present invention, the organic solvent is preferably at least one selected from the group consisting of tetrahydrofuran, propylene carbonate, methylene carbonate, and ethylene chloride.

[0037] In one embodiment of the invention, the organic solvent is tetrahydrofuran.

[0038] In one embodiment of the invention, the organic solvent is propylene carbonate.

[0039] In one embodiment of the invention, the organic solvent is methylene carbonate.

[0040] In one embodiment of the invention, the organic solvent is ethylene chloride.

[0041] In one embodiment of the invention, the organic solvent is methylene chloride.

[0042] In one embodiment of the present invention, the waste plastic is contained in an amount of 10 parts by weight to 20 parts by weight, and the organic solvent is contained in an amount of 80 parts by weight to 90 parts by weight, based on 100 parts by weight of a total weight of the first solution.

[0043] Specifically, based on 100 parts by weight of the total weight of the first solution, the waste plastic is contained in an amount of 13 to 20 parts by weight, and the organic solvent is contained in an amount of 83 to 90 parts by weight.

[0044] More specifically, based on 100 parts by weight of the total weight of the first solution, the waste plastic is contained in an amount of 14 parts by weight to 16 parts by weight, and the organic solvent is contained in an amount of 84 parts by weight to 86 parts by weight.

[0045] When the waste plastics and the organic solvent are contained in the first solution within the above-mentioned ranges, precipitation of the waste plastics does not occur and the first solution can be suitably produced.

[0046] In one embodiment of the present invention, in the step of dissolving the waste plastic in an organic solvent to prepare a first solution, the waste plastic is dissolved in the organic solvent for 1 hour to 3 hours.

[0047] Specifically, the waste plastic is dissolved in the organic solvent for 1 hour and 30 minutes to 2 hours and 30 minutes, preferably for 2 hours.

[0048] When the waste plastic is dissolved in the organic solvent for 1 to 3 hours in this manner, the waste plastic swells on the surface of the organic solvent and does not dissolve out, but is well dissolved in the organic solvent, and the first solution can be produced suitably.

[0049] In one embodiment of the present invention, the step of dissolving the waste plastic in an organic solvent to prepare the first solution may be performed at room temperature. Specifically, it may be performed at a temperature of 15° C. to 25° C. In this way, when dissolving the waste plastic in an organic solvent at a temperature of 15° C. to 25° C., the degree of evaporation of the organic solvent is low, so that the desired first solution can be prepared without a significant change in the concentration of the solution.

[0050] In one embodiment of the present invention, the method further comprises, after the step of preparing the first solution, filtering the first solution in which dissolution is completed.

[0051] The step of filtering the first solution after the completion of dissolution uses a filter having a mesh structure with a maximum diameter of 0.45 μm to 1 μm to filter out the insoluble additives contained in the first solution, other insoluble impurities that are generated when waste plastics are used for various purposes, and other polymers.

[0052] The filter may be used without limitation as long as it meets the maximum diameter range described above and is not dissolved in the organic solvent. For example, the filter may be STERLITECH polytetrafluoroethylene (PTFE) with a maximum diameter of 0.45 μm.

[0053] When the filter satisfies the maximum diameter within the above-mentioned range, it can effectively filter out insoluble additives in the first solution after dissolution, other insoluble impurities that accompany waste plastics when they are used for various purposes, and other polymers.

[0054] In the present invention, after the step of filtering the first solution in which the dissolution has been completed, an adsorbent is added as described below.

[0055] Since additives may remain in the first solution after the above-mentioned filtering step, an adsorption purification process can be carried out using an adsorbent to regenerate waste plastic into high-purity plastic.

[0056] The additives refer to organic or inorganic dyes or pigments, heat stabilizers, antioxidants, UV stabilizers, flame retardants, antistatic agents, impact modifiers, plasticizers, lubricants, etc., other than polymer compounds added during the production of plastics, but are not limited thereto, and may refer to all additives used in the art for the production of plastics.

[0057] The antioxidant may be, for example, an Irgafos antioxidant, and the heat stabilizer may be, for example, a Tinuvin heat stabilizer.

[0058] In one embodiment of the present invention, the step of adding an adsorbent to the first solution may be a step of adding an adsorbent to the first solution and stirring for 1 to 3 hours, specifically, for 1 hour 30 minutes to 2 hours 30 minutes, preferably 2 hours.

[0059] In one embodiment of the present invention, the step of adding the adsorbent to the first solution and stirring for 1 to 3 hours may be performed at room temperature. Specifically, it may be performed at a temperature of 15° C. to 25° C. In this way, when the solution is stirred at a temperature of 15° C. to 25° C., the degree of evaporation of the organic solvent is low, so that the concentration of the solution does not change significantly.

[0060] In one embodiment of the present invention, the method further comprises removing the adsorbent after the step of adding the adsorbent to the first solution.

[0061] The step of removing the adsorbent includes removing the adsorbent using a filter including a mesh structure having a maximum diameter of 0.45 μm or more and 1 μm or less.

[0062] The filter may be used without limitation as long as it meets the maximum diameter range described above and is not dissolved in the organic solvent. For example, the filter may be STERLITECH polytetrafluoroethylene (PTFE) with a maximum diameter of 0.45 μm.

[0063] When the filter meets the maximum diameter within the aforementioned range, it can effectively remove the adsorbent.

[0064] The network structure means a skeletal structure that forms a filter.

[0065] The shape of the network structure is not particularly limited, and may be adopted without limitation as long as it satisfies the maximum diameter.

[0066] The maximum diameter refers to the longest line segment among the line segments that passes through the center of each of the figures constituting the network structure and connects two points on the periphery of the figure. The center of the figure may refer to the center of gravity.

[0067] By performing the step of removing the adsorbent, additives remaining in the waste plastic contained in the first solution can be primarily removed, thereby further increasing the purity of the recycled plastic.

[0068] In one embodiment of the invention, the adsorbent is activated carbon; activated carbon pretreated with hydrochloric acid, sulfuric acid, or phosphoric acid; acid clay; diatomaceous earth; zeolite; silica gel; alumina; magnesium silicate (MgO3Si), or an ion exchange resin, or a combination thereof.

[0069] When the adsorbent is pretreated with an acid solution, it is modified to be polar and can adsorb additives. When the adsorbent contains substituents such as a hydroxyl group (-OH) or a carboxyl group (-COOH), it can also adsorb the polar substituents of the additives.

[0070] In one embodiment of the present invention, the adsorbent may be activated charcoal, which may be, but is not limited to, Activated charcoal powder (Cas no. 7440-44-0) manufactured by DUKSAN Science.

[0071] In one embodiment of the present invention, the activated carbon may be pretreated with hydrochloric acid, sulfuric acid, or phosphoric acid.

[0072] The pretreatment means that the activated carbon is brought into contact with an acid solution containing hydrochloric acid, sulfuric acid, or phosphoric acid, and then washed with distilled water to modify the surface of the activated carbon. The activated carbon may be brought into contact with the acid solution by immersing the activated carbon in the acid solution or by passing the acid solution over the activated carbon. Specifically, the activated carbon pretreated with hydrochloric acid, sulfuric acid, or phosphoric acid may be C4386 pretreated with hydrochloric acid, or C5510 pretreated with sulfuric acid and phosphoric acid, both of which are available from Sigma-Aldrich.

[0073] In one embodiment of the present invention, the activated carbon has a particle size of 100 mesh or less. Specifically, the activated carbon may have a particle size of 4 mesh or more and 100 mesh or less. More specifically, the activated carbon may have a particle size of 4 mesh or more and 12 mesh or less, 12 mesh or more and 20 mesh or less, or 20 mesh or more and 40 mesh or less. When the activated carbon satisfies the above particle size, it can effectively adsorb additives. The activated carbon having a particle size of 100 mesh or less may be obtained from Sigma-Aldrich or Oi Chemical Industries, Ltd.

[0074] In one embodiment of the present invention, the adsorbent may be acid clay, which may be, but is not limited to, Cas no. 68333-91-5 manufactured by DUKSAN.

[0075] In one embodiment of the present invention, the adsorbent may be diatomaceous earth, which may be, but is not limited to, Celite® 545 Cas no. 68855-54-9 from Sigma-aldrich.

[0076] In one embodiment of the present invention, the adsorbent may be a zeolite, which may be, but is not limited to, CBV 5524G Cas no. 1318-02-1 manufactured by Zeolyst.

[0077] In one embodiment of the present invention, the adsorbent may be silica gel, which may be, but is not limited to, silica gel 60 Cas no. 7631-86-9 manufactured by Merck.

[0078] In one embodiment of the present invention, the adsorbent may be alumina, which may be, but is not limited to, Aluminium oxide, basic powder Cas no. 1344-28-1 manufactured by Baker.

[0079] In one embodiment of the present invention, the adsorbent may be magnesium silicate (MgO3Si, Florisil), which may be, but is not limited to, Florisil® Cas no. 1343-88-0 from Sigma-aldrich.

[0080] In one embodiment of the present invention, the adsorbent may be an ion exchange resin, which may be, but is not limited to, Amberlite IRC120H, Cas no. 39389-20-3, manufactured by Sigma-Aldrich.

[0081] In one embodiment of the present invention, the adsorbent may be a combination of two or more selected from the group consisting of activated carbon; activated carbon pretreated with hydrochloric acid, sulfuric acid, or phosphoric acid; acid clay; diatomaceous earth; zeolite; silica gel; alumina; magnesium silicate (MgO3Si), and ion exchange resin.

[0082] In one embodiment of the present invention, the adsorbent may be a combination of two or more selected from the group consisting of activated carbon; acid clay; silica gel; alumina, and magnesium silicate (MgO3Si).

[0083] In one embodiment of the present invention, the adsorbent may be a combination of three or more selected from the group consisting of activated carbon; acid clay; silica gel; alumina, and magnesium silicate (MgO3Si).

[0084] In one embodiment of the invention, the adsorbent may include activated carbon; acid clay; and magnesium silicate (MgO3Si).

[0085] When the adsorbent contains two or more materials, the materials may be used as a physical mixture.

[0086] In one embodiment of the present invention, the adsorbent may consist of activated carbon; acid clay, and magnesium silicate (MgO3Si).

[0087] When the adsorbent includes activated carbon, acid clay, and magnesium silicate (MgO3Si), the activated carbon and acid clay can remove impurities other than plastic dissolved in the first solution after filtering by adsorption, and the magnesium silicate (MgO3Si) can selectively remove the oxidized parts of the plastic.

[0088] In an embodiment of the present invention, the adsorbent may be included in an amount of 0.5 parts by weight to 8 parts by weight, based on 100 parts by weight of a total weight of the first solution.

[0089] Specifically, the adsorbent may be included in an amount of 0.5 parts by weight to 7 parts by weight based on 100 parts by weight of the total weight of the first solution.

[0090] More specifically, the adsorbent may be included in an amount of 0.5 parts by weight to 6 parts by weight based on 100 parts by weight of the total weight of the first solution.

[0091] When the adsorbent is contained in the first solution in the above-mentioned range, additives remaining in the first solution can be effectively removed and processability can be maintained.

[0092] In one embodiment of the present invention, the adsorbent may be activated carbon, and may be included in an amount of 0.5 parts by weight to 8 parts by weight, based on 100 parts by weight of the total weight of the first solution.

[0093] In one embodiment of the present invention, the adsorbent may be activated carbon, and may be included in an amount of 0.5 parts by weight to 6 parts by weight, based on 100 parts by weight of the total weight of the first solution.

[0094] In one embodiment of the present invention, the adsorbent may be activated carbon, and may be included in an amount of 1 part by weight to 5 parts by weight, based on 100 parts by weight of the total weight of the first solution.

[0095] In one embodiment of the present invention, the adsorbent may be activated carbon, and may be included in an amount of 1 part by weight to 4 parts by weight, based on 100 parts by weight of the total weight of the first solution.

[0096] In one embodiment of the present invention, the adsorbent is acid clay and may be included in an amount of 0.5 parts by weight to 8 parts by weight based on 100 parts by weight of the total weight of the first solution.

[0097] In one embodiment of the present invention, the adsorbent is acid clay and may be included in an amount of 0.5 parts by weight to 6 parts by weight based on 100 parts by weight of the total weight of the first solution.

[0098] In one embodiment of the present invention, the adsorbent is acid clay and may be included in an amount of 1 part by weight to 5 parts by weight based on 100 parts by weight of the total weight of the first solution.

[0099] In one embodiment of the present invention, the adsorbent is acid clay and may be included in an amount of 1 part by weight to 4 parts by weight based on 100 parts by weight of the total weight of the first solution.

[0100] In one embodiment of the present invention, the adsorbent is acid clay and may be included in an amount of 1 part by weight to 3 parts by weight based on 100 parts by weight of the total weight of the first solution.

[0101] In one embodiment of the present invention, the adsorbent may be diatomaceous earth and may be included in an amount of 0.5 parts by weight to 8 parts by weight, based on 100 parts by weight of the total weight of the first solution.

[0102] In one embodiment of the present invention, the adsorbent may be diatomaceous earth and may be included in an amount of 0.5 parts by weight to 6 parts by weight, based on 100 parts by weight of the total weight of the first solution.

[0103] In one embodiment of the present invention, the adsorbent may be diatomaceous earth and may be included in an amount of 1 part by weight to 5 parts by weight based on 100 parts by weight of the total weight of the first solution.

[0104] In one embodiment of the present invention, the adsorbent may be diatomaceous earth and may be included in an amount of 1 part by weight to 4 parts by weight based on 100 parts by weight of the total weight of the first solution.

[0105] In one embodiment of the present invention, the adsorbent may be zeolite and may be included in an amount of 0.5 parts by weight to 8 parts by weight, based on 100 parts by weight of the total weight of the first solution.

[0106] In one embodiment of the present invention, the adsorbent may be zeolite and may be included in an amount of 0.5 parts by weight to 6 parts by weight, based on 100 parts by weight of the total weight of the first solution.

[0107] In one embodiment of the present invention, the adsorbent may be zeolite and may be included in an amount of 1 part by weight to 5 parts by weight based on 100 parts by weight of the total weight of the first solution.

[0108] In one embodiment of the present invention, the adsorbent may be zeolite and may be included in an amount of 1 part by weight to 4 parts by weight based on 100 parts by weight of the total weight of the first solution.

[0109] In one embodiment of the present invention, the adsorbent may be silica gel, and may be included in an amount of 0.5 parts by weight to 8 parts by weight, based on 100 parts by weight of the total weight of the first solution.

[0110] In one embodiment of the present invention, the adsorbent may be silica gel, and may be included in an amount of 0.5 parts by weight to 6 parts by weight, based on 100 parts by weight of the total weight of the first solution.

[0111] In one embodiment of the present invention, the adsorbent may be silica gel, and may be included in an amount of 1 part by weight to 5 parts by weight based on 100 parts by weight of the total weight of the first solution.

[0112] In one embodiment of the present invention, the adsorbent may be silica gel, and may be included in an amount of 1 part by weight to 4 parts by weight, based on 100 parts by weight of the total weight of the first solution.

[0113] In one embodiment of the present invention, the adsorbent may be alumina and may be included in an amount of 0.5 parts by weight to 8 parts by weight based on 100 parts by weight of the total weight of the first solution.

[0114] In one embodiment of the present invention, the adsorbent may be alumina, and may be included in an amount of 0.5 parts by weight to 6 parts by weight, based on 100 parts by weight of the total weight of the first solution.

[0115] In one embodiment of the present invention, the adsorbent may be alumina, and may be included in an amount of 1 part by weight to 5 parts by weight based on 100 parts by weight of the total weight of the first solution.

[0116] In one embodiment of the present invention, the adsorbent may be alumina and may be included in an amount of 1 part by weight to 4 parts by weight based on 100 parts by weight of the total weight of the first solution.

[0117] In one embodiment of the present invention, the adsorbent may be alumina and may be included in an amount of 2 parts by weight to 4 parts by weight based on 100 parts by weight of the total weight of the first solution.

[0118] In an embodiment of the present invention, the adsorbent is magnesium silicate (MgO3Si) and may be included in an amount of 0.5 parts by weight to 8 parts by weight based on 100 parts by weight of the total weight of the first solution.

[0119] In an embodiment of the present invention, the adsorbent is magnesium silicate (MgO3Si) and may be included in an amount of 0.5 parts by weight to 6 parts by weight based on 100 parts by weight of the total weight of the first solution.

[0120] In an embodiment of the present invention, the adsorbent is magnesium silicate (MgO3Si) and may be included in an amount of 1 part by weight to 5 parts by weight based on 100 parts by weight of the total weight of the first solution.

[0121] In an embodiment of the present invention, the adsorbent is magnesium silicate (MgO3Si) and may be included in an amount of 1 part by weight to 4 parts by weight based on 100 parts by weight of the total weight of the first solution.

[0122] In an embodiment of the present invention, the adsorbent is magnesium silicate (MgO3Si) and may be included in an amount of 0.5 parts by weight to 2 parts by weight based on 100 parts by weight of the total weight of the first solution.

[0123] In one embodiment of the present invention, the adsorbent is an ion exchange resin, and may be included in an amount of 0.5 parts by weight to 8 parts by weight, based on 100 parts by weight of the total weight of the first solution.

[0124] In one embodiment of the present invention, the adsorbent is an ion exchange resin, and may be included in an amount of 0.5 parts by weight to 6 parts by weight, based on 100 parts by weight of the total weight of the first solution.

[0125] In one embodiment of the present invention, the adsorbent is an ion exchange resin, and may be included in an amount of 1 part by weight to 5 parts by weight based on 100 parts by weight of the total weight of the first solution.

[0126] In one embodiment of the present invention, the adsorbent is an ion exchange resin, and may be included in an amount of 1 part by weight to 4 parts by weight, based on 100 parts by weight of the total weight of the first solution.

[0127] In one embodiment of the present invention, the adsorbent may include, based on 100 parts by weight of a total weight of the first solution, 0.5 parts by weight to 3 parts by weight of the activated carbon, 0.5 parts by weight to 4 parts by weight of acid clay, and 0.5 parts by weight to 2 parts by weight of magnesium silicate (MgO3Si).

[0128] In one embodiment of the present invention, the adsorbent may include 1 to 3 parts by weight of the activated carbon, 1 to 4 parts by weight of acid clay, and 0.5 to 1 part by weight of magnesium silicate (MgOSi), based on 100 parts by weight of a total weight of the first solution.

[0129] In one embodiment of the present invention, the adsorbent may include 1 to 2 parts by weight of the activated carbon, 1 to 3 parts by weight of acid clay, and 0.5 to 1 part by weight of magnesium silicate (MgOSi), based on 100 parts by weight of a total weight of the first solution.

[0130] In one embodiment of the present invention, the adsorbent may include 2 parts by weight of the activated carbon, 3 parts by weight of acid clay, and 1 part by weight of magnesium silicate (MgO3Si), based on 100 parts by weight of a total weight of the first solution.

[0131] In one embodiment of the present invention, the adsorbent may include 1.5 parts by weight of the activated carbon, 2 parts by weight of acid clay, and 0.5 parts by weight of magnesium silicate (MgO3Si), based on 100 parts by weight of a total weight of the first solution.

[0132] In one embodiment of the present invention, the adsorbent may include 1 part by weight of the activated carbon, 1 part by weight of acid clay, and 0.5 parts by weight of magnesium silicate (MgO3Si), based on a total weight of 100 parts by weight of the first solution.

[0133] After the step of removing the adsorbent, a compound having a Hansen Solubility Parameter (HSP) of 5 to 14 in polycarbonate is added to the first solution, based on 100 parts by weight of the total weight of the first solution, thereby secondarily removing the additives contained in the first solution and solidifying the polycarbonate.

[0134] In other words, the additives are primarily removed by the adsorbent, and then a compound with a Hansen Solubility Parameter (HSP) of 5 to 14 in polycarbonate is added to secondarily remove the additives, allowing waste plastic to be recycled into high-purity plastic.

[0135] In one embodiment of the present invention, the first solution may contain 60 parts by weight to 100 parts by weight of a compound having a Hansen Solubility Parameter (HSP) in polycarbonate of 5 to 14, based on 100 parts by weight of the total weight of the first solution.

[0136] When the compound having a Hansen Solubility Parameter (HSP) of 5 to 14 in the polycarbonate is contained in an amount of more than 100 parts by weight, a yield similar to that of the compound containing 60 to 100 parts by weight can be expected, but the effect is negligible, and the use of a large amount of solvent may have a detrimental effect on economy and processability.

[0137] In other words, adding a compound having a Hansen Solubility Parameter (HSP) of 5 to 14 in polycarbonate in an amount of 60 to 100 parts by weight is the optimal addition condition that shows excellent effects when economic efficiency is taken into consideration.

[0138] In one embodiment of the present invention, the first solution may contain 70 to 90 parts by weight of a compound having a Hansen Solubility Parameter (HSP) of 5 to 14 in polycarbonate, based on 100 parts by weight of the total weight of the first solution.

[0139] In one embodiment of the present invention, the first solution may contain 80 to 90 parts by weight of a compound having a Hansen Solubility Parameter (HSP) of 5 to 14 in polycarbonate, based on 100 parts by weight of the total weight of the first solution.

[0140] In one embodiment of the present invention, the first solution may contain 83 to 87 parts by weight of a compound having a Hansen Solubility Parameter (HSP) of 5 to 14 in polycarbonate, based on 100 parts by weight of the total weight of the first solution.

[0141] In one embodiment of the present invention, the first solution may contain 85 parts by weight of a compound having a Hansen Solubility Parameter (HSP) of 5 to 14 in polycarbonate, based on 100 parts by weight of the total weight of the first solution.

[0142] In one embodiment of the present invention, the compound having a Hansen Solubility Parameter (HSP) of 5 to 14 in polycarbonate is a hydrocarbon compound containing one or more selected from the group consisting of alcohol, ketone, ether, cycloalkane, ester, carboxylic acid, and nitrile group.

[0143] The Hansen solubility parameter for the polycarbonate can be calculated by taking into consideration the degree of bonding in the polycarbonate material, specifically, the non-polar dispersion bond, the dipole-dipole force, and the hydrogen bonding force.

[0144] Specifically, the compound having a Hansen Solubility Parameter (HSP) of 5 to 14 in polycarbonate is a hydrocarbon compound having 1 to 10 carbon atoms and containing at least one selected from the group consisting of alcohol, ketone, ether, cycloalkane, ester, carboxylic acid, and nitrile group.

[0145] More specifically, the compound having a Hansen Solubility Parameter (HSP) of 5 to 14 in polycarbonate is a hydrocarbon compound having 1 to 5 carbon atoms and containing at least one selected from the group consisting of alcohol, ketone, ester, and nitrile groups.

[0146] Preferably, the compound having a Hansen Solubility Parameter (HSP) of 5 to 14 in polycarbonate is ethanol, acetone, ethyl acetate, or acetonitrile.

[0147] In one embodiment of the present invention, the compound having a Hansen Solubility Parameter (HSP) of 5 to 14 in polycarbonate is ethanol.

[0148] In one embodiment of the present invention, the compound having a Hansen Solubility Parameter (HSP) of 5 to 14 in polycarbonate is acetone.

[0149] In one embodiment of the present invention, the compound having a Hansen Solubility Parameter (HSP) of 5 to 14 in polycarbonate is ethyl acetate.

[0150] In one embodiment of the present invention, the compound having a Hansen Solubility Parameter (HSP) of 5 to 14 for polycarbonate is acetonitrile.

[0151] In one embodiment of the invention, the weight percentage of waste plastics relative to the total weight of the first solution is less than 20 wt%, and the weight percentage of recrystallized plastics relative to the total weight of the first solution is less than 20 wt%.

[0152] In one embodiment of the invention, the weight percentage of waste plastics relative to the total weight of the first solution is 15 wt% or less, and the weight percentage of recrystallized plastics relative to the total weight of the first solution is 15 wt% or less.

[0153] The weight percentage of the waste plastic relative to the total weight of the first solution may be 1 wt % or more.

[0154] When the percentage concentration of the first solution satisfies the above-mentioned range, the waste plastic or recrystallized plastic can be sufficiently dissolved in the solvent and can be suitably maintained in a saturated state.

[0155] After adding a compound having a Hansen Solubility Parameter (HSP) of 5 to 14 for the polycarbonate to the first solution, a step of recovering the recrystallized polycarbonate is performed.

[0156] In one embodiment of the present invention, the step of recovering the recrystallized polycarbonate may further include a step of precipitating a plastic from the recrystallized polycarbonate into a powder or granule type; and a step of processing the precipitate to obtain a recycled plastic. The method of precipitating and processing is not particularly limited, and a method applied in the art may be appropriately adopted.

[0157] The plastics recycled using the waste plastic recycling process of the present invention do not contain any organic or inorganic dye or pigment additives and are colorless.

[0158] In one embodiment of the present specification, the dL, da, db, and y values ​​measured by a spectrophotometer for dichloromethane in a pure solvent state are used as a reference, and the dL, da, db, and y values ​​measured by a spectrophotometer for a solution in which the plastic recycled by the waste plastic recycling process is dissolved in dichloromethane solvent at 5 wt% satisfy the following relationship.

[0159]

number

[0160] The spectrophotometer may be an X-rite Ci7600 Color Spectrophotometer.

[0161] Specifically, the above formula represents the difference between the dL, da, and db values ​​measured by a spectrophotometer for dichloromethane in a pure solvent state and the dL, da, and db values ​​measured by a spectrophotometer for the recycled plastic, after setting the values ​​to a reference value (0). In the formula, y represents the yellow index.

[0162] The dichloromethane in a pure solvent state means dichloromethane that does not contain any solute.

[0163] In this specification, when the dL, da, db, and y values ​​measured by the spectrophotometer satisfy the above-mentioned relational expressions, this may mean colorless, which does not show any specific color.

[0164] Another embodiment of the present specification provides a method for producing recycled plastic, comprising the step of recycling the waste plastic.

[0165] In addition to the recycling process of the waste plastic, the method for producing recycled plastic may further employ other processes necessary for producing recycled plastic, which may be processes well known in the art. EXAMPLES

[0166] The present invention will be illustrated in more detail with reference to the following examples. The present invention is not limited to these examples, and the examples according to the present invention may be modified in various different forms, and the scope of the present invention should not be construed as being limited to the following examples. The examples of the present invention are provided to more completely explain the present invention to those having average knowledge in the art.

[0167] Examples 1 to 30 15 parts by weight of waste polycarbonate was dissolved in 85 parts by weight of the organic solvent shown in Table 1 below at room temperature for 2 hours to produce 100 parts by weight of a first solution. The waste polycarbonate used had a weight average molecular weight of 40,000 g / mol to 60,000 g / mol, a polydispersity index (PDI) of 1.8 to 3, and a melt flow rate (MFR) of 10 to 28.

[0168] After the first solution had been completely dissolved, it was filtered using a STERLITECH polytetrafluoroethylene (PTFE) filter having a mesh structure with a maximum diameter of 0.45 μm, and then activated carbon shown in Table 1 below was added as an adsorbent and stirred for 2 hours.

[0169] After completing the stirring, the adsorbent was removed using a STERLITECH polytetrafluoroethylene (PTFE) filter containing a mesh structure with a maximum diameter of 0.45 μm, and then a compound having a Hansen Solubility Parameter (HSP) of 5 to 14 in polycarbonate shown in Table 1 below was added, and then the recrystallized polycarbonate was collected.

[0170] Comparative Examples 1 to 6 The same procedure as in the above-mentioned examples was carried out, except that the compounds and adsorbents having a Hansen Solubility Parameter (HSP) of 5 to 14 in polycarbonate were added in parts by weight as shown in Table 1 below.

[0171] [Table 1A] [Table 1B]

[0172] In Table 1, the adsorbents used are specifically as follows:

[0173] -Activated charcoal: Activated charcoal powder (Cas no. 7440-44-0) manufactured by DUKSAN Science -Acid clay: Cas no. 68333-91-5 manufactured by DUKSAN Magnesium silicate: Florisil® Cas no. 1343-88-0 from Sigma-Aldrich -Silica gel: Merck silica gel 60 Cas no. 7631-86-9 -Alumina: Baker aluminum oxide, basic powder Cas no. 1344-28-1

[0174] Experimental Example The recrystallized plastic was precipitated into a powder type plastic, which was then processed into pellets using an extruder to obtain recycled plastic.

[0175] The color of the recycled plastic was measured under the following conditions and is shown in Table 2 below.

[0176] - Measurement of recycled plastics using a spectrophotometer: Using an X-rite Ci7600 Color Spectrophotometer, first put dichloromethane in a pure solvent state into a measurement cuvette and set the measured dL, da, db, and y values ​​as the reference value (0). Then, put a solution of the recycled plastic dissolved in dichloromethane at 5 wt% into the measurement cuvette and record the difference between these values ​​and the dL, da, and db values.

[0177] [Table 2]

[0178] According to Table 2, in the case of Examples 1 to 30 according to the embodiment of the present invention, it was confirmed that the recycled plastics were colorless since the measurement result values ​​by the spectrophotometer in Table 2 satisfied the relational expressions, and additives such as organic or inorganic dyes or pigments were removed without being contained.

[0179] In addition, in the case of Examples 27 to 28, in which 110 parts by weight and 120 parts by weight of a compound having a Hansen Solubility Parameter (HSP) of 5 to 14 in polycarbonate were used, the results of the measurement using a spectrophotometer satisfied the above-mentioned relational expression, but it was confirmed that the difference in effect was negligible compared to the case in which 60 parts by weight to 100 parts by weight were used.

[0180] In addition, in the case of Comparative Example 1, in which no adsorbent was added, the dL and db values ​​did not satisfy the relationship and the plastic was not colorless, confirming that the recycled plastic contained additives or impurities.

[0181] In addition, in the case of Comparative Examples 2 to 4 in which 10 parts by weight, 20 parts by weight, and 30 parts by weight of a compound having a Hansen Solubility Parameter (HSP) of 5 to 14 in polycarbonate were used, the amount of the compound having a Hansen Solubility Parameter (HSP) of 5 to 14 in polycarbonate added was too small, so that the recrystallization of the polycarbonate was not smooth and a solid could not be obtained.

[0182] In addition, in the case of Comparative Examples 5 and 6, in which 40 and 50 parts by weight of compounds with a Hansen Solubility Parameter (HSP) of 5 to 14 in polycarbonate were used, the dL value did not satisfy the relational equation, the material was not colorless, and the solid yield was about half that of Comparative Example 1. It was therefore confirmed that these were not suitable for the process and that the recycled plastic contained additives or impurities.

[0183] This confirms that when the waste plastic recycling process according to the present invention is applied, recycled plastic with excellent purity can be obtained.

Claims

1. Dissolving waste plastic in an organic solvent to prepare a first solution; adding an adsorbent to the first solution; removing the adsorbent using a filter containing a mesh structure having a maximum diameter of 0.45 μm or more and 1 μm or less; Adding 60 to 100 parts by weight of a compound having a Hansen Solubility Parameter (HSP) of 5 to 14 in polycarbonate based on 100 parts by weight of the total weight of the first solution to recrystallize the plastic; and Recovering the recrystallized plastic. A waste plastic recycling process, including:

2. The waste plastic recycling process according to claim 1 , further comprising a step of filtering the first solution after the step of producing the first solution.

3. The process for recycling waste plastics according to claim 1, wherein the recrystallized plastic is polycarbonate.

4. The process for recycling waste plastics according to claim 1, wherein the organic solvent is a cyclic ether solvent, a linear or cyclic carbonate solvent, or a hydrocarbon solvent having 1 to 8 carbon atoms and containing one or more halogens.

5. The compound having a Hansen Solubility Parameter (HSP) of 5 to 14 in polycarbonate is a hydrocarbon compound containing one or more selected from the group consisting of alcohol, ketone, ether, cycloalkane, ester, carboxylic acid, and nitrile groups. The process for recycling waste plastics according to claim 1.

6. The adsorbents include activated carbon; activated carbon pretreated with hydrochloric acid, sulfuric acid, or phosphoric acid; acid clay; diatomaceous earth; zeolite; silica gel; alumina; magnesium silicate (MgO 3 2. The process for recycling waste plastics according to claim 1, wherein the fluorine-containing compound is a fluorine-containing cation exchange resin, ... or a combination thereof.

7. The adsorbents include activated carbon, acid clay, and magnesium silicate (MgO 3 The process for recycling waste plastics according to claim 1, further comprising:

8. The process for recycling waste plastics according to claim 1 , wherein the adsorbent is added in an amount of 0.5 parts by weight to 8 parts by weight based on 100 parts by weight of the total weight of the first solution.

9. The adsorbent contains 0.5 to 3 parts by weight of the activated carbon, 0.5 to 4 parts by weight of acid clay, and magnesium silicate (MgO 3 The waste plastic regeneration process according to claim 7, further comprising 0.5 to 2 parts by weight of sulphuric acid (Si).

10. The process for recycling waste plastics according to claim 1, wherein the waste plastics are contained in an amount of 10 to 20 parts by weight, and the organic solvent is contained in an amount of 80 to 90 parts by weight, based on a total weight of 100 parts by weight of the first solution.

11. 2. The process for recycling waste plastic according to claim 1, wherein the compound having a Hansen Solubility Parameter (HSP) of 5 to 14 in polycarbonate is contained in an amount of 80 to 90 parts by weight based on 100 parts by weight of a total weight of the first solution.

12. 2. The waste plastic recycling process of claim 1, wherein the weight percentage of the waste plastic to the total weight of the first solution is 20 wt% or less, and the weight percentage of the recrystallized plastic to the total weight of the first solution is 20 wt% or less.

13. A method for producing recycled plastic, comprising a recycling step of the waste plastic according to any one of claims 1 to 12.

Citation Information

Patent Citations

  • Method for recycling aromatic polycarbonate

    JP1999152371A

  • Recycling of molded item of polymer resin containing alycyclic structure

    JP1999293030A

  • Processing method for information recording medium

    JP2005293710A

  • Method for chemical recycling waste plastics including crystallization

    KR1020210067555A

  • Methods useful for recovering polymers from electronic and other wastes

    US20170022346A1